2018
DOI: 10.7717/peerj.4893
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics, laboratory parameters, treatment protocols, and outcomes of pancreatic cancer: a retrospective cohort study of 1433 patients in China

Abstract: ObjectivesThe prognosis of people with pancreatic cancer is extremely unfavorable. However, the prognostic factors remain largely undefined. We aimed to perform comprehensive analyses of clinicopathologic characteristics, laboratory parameters, and treatment protocols for exploring their role as prognostic factors of pancreatic cancer.MethodsPatients diagnosed with pancreatic cancer and hospitalized at the China National Cancer Center between April 2006 and May 2016 were enrolled in this retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
6
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
7
6
2
5
Order By: Relevance
“…The two major findings in this study are, first, FGFR1 could be a promising prognostic marker for periampullary cancers, and second, peritumoral fibrosis was associated with tumor recurrence in periampullary cancer patients. We also confirmed significant relationship between overall survival and previously known clinicopathological prognostic markers, such as age, location, T stage, gross type, size, N stage, M stage, lymphatic invasion, vascular invasion, perineural invasion, histological differentiation, inflammation and the staining pattern of the IHC markers (CK20, CDX2), as described in the literature [1,12].…”
Section: Discussionsupporting
confidence: 88%
“…The two major findings in this study are, first, FGFR1 could be a promising prognostic marker for periampullary cancers, and second, peritumoral fibrosis was associated with tumor recurrence in periampullary cancer patients. We also confirmed significant relationship between overall survival and previously known clinicopathological prognostic markers, such as age, location, T stage, gross type, size, N stage, M stage, lymphatic invasion, vascular invasion, perineural invasion, histological differentiation, inflammation and the staining pattern of the IHC markers (CK20, CDX2), as described in the literature [1,12].…”
Section: Discussionsupporting
confidence: 88%
“…The two major findings in this study are, first, FGFR1 could be a promising prognostic marker for periampullary cancers, and second, peritumoral fibrosis was associated with tumor recurrence in periampullary cancer patients. We also confirmed significant relationship between overall survival and previously known clinicopathological prognostic markers, such as age, location, T stage, gross type, size, N stage, M stage, lymphatic invasion, vascular invasion, perineural invasion, histological differentiation, inflammation and the staining pattern of the IHC markers (CD20, CDX2), as described in the literature [1,12].…”
Section: Discussionsupporting
confidence: 88%
“…Zhang et al's study explored the effect of hypertension on survival. They found that there was a reduction in short-term survival (p=0.031) [9]. Furthermore, our data heavily supports this, as almost 60% of patients who died had hypertension (p=0.027).…”
Section: Discussionsupporting
confidence: 85%
“…The risk of postoperative complications for patients with T2DM and pancreatic adenocarcinoma who underwent resection was high in the long term [6]. The short-term outcome was also affected by lower survival [9]. However, our study did not show any survival advantage for patients with or without T2DM (p=0.289).…”
Section: Discussioncontrasting
confidence: 66%